Searching for nearby diffuse dwarf galaxies in the COSMOS field - Shi, Dong Dong; Zheng, Xian Zhong; Pan, Zhizheng; Luo, Yu; Deng, Hongxia; Hua, Qunzhi; Luo, Xinyu; Wu, Qiming (Frontiers in Astronomy and Space Sciences, 2025)
It remains challenging to systematically survey nearby diffuse dwarf galaxies and address the formation mechanism of this population distinguishing from regular ones. We carry out a pilot search for these galaxies in the COSMOS field using the deep HST/F814W imaging data. We report three diffuse dwarf galaxies satisfying the criteria: (1) redshift z<0.2, (2) effective radius re>1.′′0, and (3) central surface brightness μ0>24 mag arcsec−2. Two of the three galaxies, COSMOS-UDG1 and COSMOS-UDG2, are recognized as ultra-diffuse galaxies (UDGs) with redshift z=0.130 and 0.049, respectively. The third galaxy, COSMOS-dw1, is spectroscopically confirmed as a dwarf galaxy at z=0.004. We derive the physical properties through fitting their spectral energy distributions (SEDs) extracted from deep multiwavelength observations. COSMOS-dw1 has a stellar mass of 5.6−2.7+2.5×106M⊙, harboring neutral hydrogen gas of mass 4.90±0.90×106M⊙, hinting that this galaxy may be in the nascent stages of quenching. The estimated dynamical mass of 3.4×107 M⊙ further suggests that COSMOS-dw1 is predominantly of dark matter. COSMOS-UDG1 and COSMOS-UDG2 exhibit comparable stellar masses of ∼2×108M⊙. Notably, COSMOS-UDG1 is younger and more metal-rich than COSMOS-UDG2 and COSMOS-dw1. Conversely, COSMOS-UDG2 and COSMOS-dw1 have similar stellar metallicities, yet COSMOS-UDG2 is older than COSMOS-dw1. All three galaxies adhere to the stellar mass-metallicity relation (MZR) for dwarf galaxies in the local Universe, implying they belong to the dwarf galaxy population.